SARS-CoV-2 Mpro inhibition by a zinc ion: structural features and hints for drug design. Issue 64 (19th July 2021) - Grifagni, Deborah; Calderone, Vito; Giuntini, Stefano; Cantini, Francesca; Fragai, Marco; Banci, Lucia
Abstract : The first structure of the SARS-CoV-2 main protease in complex with an isolated zinc ion provides solid ground for the design of potent and selective metal-conjugated inhibitors. Abstract : Structural data on the SARS-CoV-2 main protease in complex with a zinc-containing organic inhibitor are already present in the literature and gave hints on the presence of a zinc binding site involving the catalytically relevant cysteine and histidine residues. In this paper, the structural basis of ionic zinc binding to the SARS-CoV-2 main protease has been elucidated by X-ray crystallography. The zinc binding affinity and its ability to inhibit the SARS-CoV-2 main protease have been investigated. These findings provide solid ground for the design of potent and selective metal-conjugated inhibitors of the SARS-CoV-2 main protease.